Supply-side constraints to technology adoption: The market for energy-efficient cookstoves in rural Senegal - Maximiliane Sievert; Jörg Ankel-Peters; Marc Jeuland; Luciane Lenz; Ousmane Ndiaye; Faraz Usmani (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Diffusion of technology that improves welfare is a global policy priority. We study the market for energyefficient biomass cookstoves in rural Senegal. Our surveys cover stove producers and intermediary vendors on the supply side and also elicit demand from rural households using real-purchase offers. We randomly relax supply-side constraints among vendors by providing demand information, marketing materials, and a transportation grant to bridge the last mile to villages where customers reside. We find that the transportation grant increases vendor sales, but overall, our results indicate that market conditions are challenging: markups are lower than for competing products and demand is volatile. This combination of high risks and low profits need to be addressed by policy interventions if large-scale diffusion is the goal. – – Die Verbreitung von neuen Technologien, die den Wohlstand erhöhen, ist eine globale Priorität. Wir untersuchen den Markt für energieeffiziente Biomasse-Herde im ländlichen Senegal. Wir untersuchen Herdproduzenten und Zwischenhändler auf der Angebotsseite und erheben die Nachfrage ländlicher Haushalte durch reale Kaufangebote. Wir lockern die angebotsseitigen Restriktionen für die Verkäufer, indem wir ihnen Informationen über die Nachfrage, Marketingmaterial und einen Transportkostenzuschuss zur Überbrückung der letzten Meile zu den Dörfern, in denen die Kunden leben, zur Verfügung stellen. Wir stellen fest, dass der Transportkostenzuschuss den Umsatz der Verkäufer erhöht, aber insgesamt deuten unsere Ergebnisse darauf hin, dass die Marktbedingungen schwierig sind: Die Gewinnspannen sind geringer als bei Konkurrenzprodukten und die Nachfrage ist volatil. Diese Kombination aus hohen Risiken und geringen Gewinnen muss durch politische Interventionen angegangen werden, wenn eine großflächige Verbreitung angestrebt wird.
Keywords: D22; D47; O13; Q28; 330; Technology adoption; supply side; improved cooking; liquidity constraints